The Profile of P63 Expression and Epstein-Barr-Encoded RNA (EBER) Distribution in Primary Central Nervous System Lymphoma: A Retrospective Bi-Center Study - Kristiani, Erna; Marisca, Stephanie; Suharyani, Sally; Dermawan, Kevin; Widodo, Stephanie T.; Ham, Maria F.; Harahap, Agnes S.; Susanto, Eka; Tjahjadi, Hartono; July, Julius (Medicinus, 2025)
Background : Primary central nervous system lymphoma (PCNSL) is a type of lymphoma occurring around 0.5 – 1.2% of all intracranial neoplasms. However, recent epidemiological research shows a threefold increase in the number of cases. The Epstein-Barr virus (EBV) and PCNSL are both associated with the condition of immunosuppression or immunodeficiency, which often found to have a significant relationship with each other. Moreover, the TP63 mutation is associated with a poor prognosis. Methods : This is a descriptive study to assess the expression of TP63 and EBER on PCNSL, and present the characteristics of the disease. The study was conducted on 25 cases from two health centers with the most cases of brain tumors in Indonesia, Siloam Hospital Lippo Village and Cipto Mangunkusumo Hospital (CMH) from 2014 to 2018, the P63 expression and EBER-1 examinations were done by 4 pathologists. A total of 25 patients, 13 (52%) patients were male, ranging from age 30 – 79, with average 57,6 years old, located mostly in the frontal lobe in 8 patients (30.9%). Result : From the research results obtained positive P63 results in 20 cases (80%), while the EBER test was negative for all 25 patients. Further analysis with software SPSS 25 proving that P63 expression is not associated with germinal center B-cell type (GCB) or non-GCB type (p-value 0,87). Neither, P63 have any association with Ki67 with p-value of 1.00. Conclusions : This study concludes that there is a possibility that PCNSL cases in Indonesia are not associated with Epstein-Barr virus infection, but most of the cases will have a poor prognosis as indicated by P63 expression.